Uji efektifitas antibakteri ekstrak buah jeruk nipis (Citrus aurantifolia) terhadap pertumbuhan Streptococcus mutans in vitro - Putu Wiswananta Parama; I Dewa Made Sukrama; Steffano Aditya Handoko (Bali Dental Journal, 2019)
Introduction: Lime fruit has been used by the society in order to prevent and cure many disease that caused by bacteria, fungus and virus infection. Lime (Citrus aurantifolia) contain some active compounds such as alkaloid, flavonoid, steroid, triterpenoid, saponin, tannin and phenolic that can inhibit the growth of bacteria. Streptococcus mutans is a Gram-Positive, facultative anaerobe bacteria that caused dental caries. The aim of this study is to know whether lime (Citrus aurantifolia) extract has an effect on Streptococcus mutans growth in vitro. Method: An experimental research has been done using Post Test Only Control Group Design method with lime (Citrus aurantifolia) extract that its antibacterial effectivity was tested on Streptococcus mutans ATCC 35668. The test method used was Kirby-Bauer disc diffusion on Muller Hinton blood agar media. The lime extract on this research obtained using maseration method with methanol 98% as the solvent. The concentration created was 40%, 60%, and 80%. Positive control used was Vancomycin and the negative control used was methanol 98%. Result: The result is inhibition zone that formed around the extract disc was increased with enchancement of the extract concentration. The average of inhibition zone in 40%; 60%; 80% concentration is 14,2; 19,6; 22,6 mm. Statistical test One Way ANOVA showed that p<0.05 that mean there is a significant difference in every extract concentration that inhibit Streptococcus mutans growth in vitro. Conclusion: Lime fruit extract (Citrus aurantifolia) with a concentration of 40%, 60%, and 80% can inhibit the growth of Streptococcus mutans in vitro.